Pengaruh Stres Kerja Dan Beban Kerja Terhadap Turnover Intention Karyawan Pada Pt Bharaduta Jaya Sakti Jakarta Selatan - Fadlan Maulana; Hira Maulida (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of job stress and workload on employee turnover intention at PT Bharaduta Jaya Sakti, both partially and simultaneously. The research employs an associative quantitative method with a population of 85 employees. The sampling technique used is saturated sampling, meaning that the entire population was selected as the sample. Data processing and analysis were conducted using SPSS version 25, with analytical methods including simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, partial T test, and simultaneous F test. The results show that job stress has a significant partial effect on turnover intention. This is evidenced by a t-value of 8,747, which is greater than the t-table value of 1,988, along with a significance level of 0.000 < 0.05, indicating that Ho1 is rejected and Ha1 is accepted. Furthermore, workload also has a significant partial effect on turnover intention, as indicated by a t-value of 8,210 > 1,988 and a significance level of 0.000 < 0.05, leading to the rejection of Ho2 and acceptance of Ha2. Simultaneously, job stress and workload significantly influence turnover intention, demonstrated by an F-value of 66,355, which exceeds the F-table value of 3,110, with a significance level of 0.000 < 0.05, resulting in the rejection of Ho3 and acceptance of Ha3. The coefficient of determination (R Square) of 0,618 indicates that job stress and workload contribute 61.8% to turnover intention, while the remaining 38.2% is influenced by other variables not examined in this study.